AtCOX10, a protein involved in haem o synthesis during cytochrome c oxidase biogenesis, is essential for plant embryogenesis and modulates the progression of senescence - Mansilla, Natanael (2015)
Cytochrome c oxidase (CcO) biogenesis requires several accessory proteins implicated, among other processes, in copper and haem a insertion. In yeast, the farnesyltransferase Cox10p that catalyses the conversion of haem b to haem o is the limiting factor in haem a biosynthesis and is essential for haem a insertion in CcO. In this work, we characterized AtCOX10, a putative Cox10p homologue from Arabidopsis thaliana. AtCOX10 was localized in mitochondria and was able to restore growth of a yeast Δcox10 null mutant on non-fermentable carbon sources, suggesting that it also participates in haem o synthesis. Plants with T-DNA insertions in the coding region of both copies of AtCOX10 could not be recovered, and heterozygous mutant plants showed seeds with embryos arrested at early developmental stages that lacked CcO activity. Heterozygous mutant plants exhibited lower levels of CcO activity and cyanide-sensitive respiration but normal levels of total respiration at the expense of an increase in alternative respiration. AtCOX10 seems to be implicated in the onset and progression of senescence, since heterozygous mutant plants showed a faster decrease in chlorophyll content and photosynthetic performance than wild-type plants after natural and darkinduced senescence. Furthermore, complementation of mutants by expressing AtCOX10 under its own promoter allowed us to obtain plants with T-DNA insertions in both AtCOX10 copies, which showed phenotypic characteristics comparable to those of wild type. Our results highlight the relevance of haem o synthesis in plants and suggest that this process is a limiting factor that influences CcO activity levels, mitochondrial respiration, and plant senescence.